Morphometric Studies of the Sweet Potato Weevil, Cylas Species- Complex in Southern Ghana - Billah, M.K.; Agbessenou, A.; Wilson, D.D.; Dekoninck, W.; Vangestel, C. (Science and Development (A Journal of the College of Basic and Applied Sciences (CBAS), University of Ghana), 2017)
The Sweet potato weevil, Cylas species, is a key pest of sweet potato, and widely distributed on the African continent. The management of the pest is limited because its taxonomic status is not clear. Populations of the same species occupying distinct localities experience different ecological and climatic pressures that might result in differentiation in traits. This study sought to identify and compare body sizes of Cylas species from four regions in southern Ghana – Central, Eastern, Greater Accra and Volta. Of the 6,686 samples collected from the four regions, two species were identified: Cylas brunneus Fabricius, and Cylas puncticollis Boheman. Twelve morphometric characters were examined and measured, of which four traits - elytra and rostrum lengths, pronotum and head widths contributed most to the variations observed. In C. puncticollis, individuals with the longest body were recorded in Greater Accra Region (7.084 ± 0.089 mm), while those in the Central Region had the smallest body size (6.786 ± 0.086 mm). Our findings suggest that distinct localities may influence changes in body size.
Journal Article
Keywords: Sweet potato; Cylas brunneus; C. puncticollis; morphometric studies; Southern Ghana